An integrative phylogenomic approach illuminates the evolutionary history of cockroaches and termites (Blattodea). Issue 1895 (30th January 2019) - Evangelista, Dominic A.; Wipfler, Benjamin; Béthoux, Olivier; Donath, Alexander; Fujita, Mari; Kohli, Manpreet K.; Legendre, Frédéric; Liu, Shanlin; Machida, Ryuichiro; Misof, Bernhard; Peters, Ralph S.; Podsiadlowski, Lars; et al.
Abstract : Phylogenetic relationships among subgroups of cockroaches and termites are still matters of debate. Their divergence times and major phenotypic transitions during evolution are also not yet settled. We addressed these points by combining the first nuclear phylogenomic study of termites and cockroaches with a thorough approach to divergence time analysis, identification of endosymbionts, and reconstruction of ancestral morphological traits and behaviour. Analyses of the phylogenetic relationships within Blattodea robustly confirm previously uncertain hypotheses such as the sister-group relationship between Blaberoidea and remaining Blattodea, and Lamproblatta being the closest relative to the social and wood-feeding Cryptocercus and termites. Consequently, we propose new names for various clades in Blattodea: Cryptocercus + termites = Tutricablattae; Lamproblattidae + Tutricablattae = Kittrickea; and Blattoidea + Corydioidea = Solumblattodea. Our inferred divergence times contradict previous studies by showing that most subgroups of Blattodea evolved in the Cretaceous, reducing the gap between molecular estimates of divergence times and the fossil record. On a phenotypic level, the blattodean ground-plan is for egg packages to be laid directly in a hole while other forms of oviposition, including ovovivipary and vivipary, arose later. Finally, other changes in egg care strategy may have allowed for the adaptation of nest building and other novelties.